Village Community Empowerment Through Oyster Mushroom Processing Training for Economic Independence - Sri Rahayu; Luluk Sulistiyo Budi; Indah Rekyani Puspitawati; Ma'ruf Pambudi Nurwantara (Jurnal Peduli Masyarakat, 2020)
Madiun Merdeka University with Higher Education Leading Community Empowerment Program did technology transfer with theme processing oyster mushroom products. The aim of this activities is to solve the weakness of oyster mushroom which is wither quickly, easily rotten, and cheap selling price, so it can improve welfare of the people at Bodag Village, Kare District, Madiun Regency. The method is: the amount of participants are 26 people that member of Tani Rejo farmers amn Mulyo farmers. The activities by following 3M healthy protocol. The activity consist of processed oyster mushroom practices, problem discussion and processing solution, business management, marketing, packaging, and product serving. The results of this activities is oyster mushroom processing training gives positive value to the people. The people give best response into this activities. The output of this activities is the people can make crispy mushroom, shredded mushroom, rendang mushroom, ca mushroom, satay mushroom, ice cream mushroom, risol mushroom, nuggets mushroom, mushroom fried rice, mushroom fried rice, mushrood tomyam, and mushroom garang asem.